2016
DOI: 10.1007/s10164-016-0473-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring African lion (Panthera leo) behavioural phenotypes: individual differences and correlations between sociality, boldness and behaviour

Abstract: This document is the author's post-print version, incorporating any revisions agreed during the peer-review process. Some differences between the published version and this version may remain and you are advised to consult the published version if you wish to cite from it.1 Exploring African lion (Panthera leo) behavioural phenotypes: individual differences and correlations between sociality, boldness and behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…Although the lion pride is a fission–fusion society with individuals dispersing and returning to the group ( VanderWaal et al, 2009 ), it is socially cohesive. Social network analysis of both captive origin and wild prides indicate that female lions are central to the social network with adult male lions most likely to receive and least likely to initiate social interactions ( Dunston et al, 2016a , b ). Male lions are not only less social than female lions, but are also larger and more aggressive than female lions.…”
Section: Discussionmentioning
confidence: 99%
“…Although the lion pride is a fission–fusion society with individuals dispersing and returning to the group ( VanderWaal et al, 2009 ), it is socially cohesive. Social network analysis of both captive origin and wild prides indicate that female lions are central to the social network with adult male lions most likely to receive and least likely to initiate social interactions ( Dunston et al, 2016a , b ). Male lions are not only less social than female lions, but are also larger and more aggressive than female lions.…”
Section: Discussionmentioning
confidence: 99%
“…Individual animals can often differ in their response to novel stimuli [12], and it is recommended that zoo animal welfare should be measured on an individual basis [20]. Indeed, both Asiatic and African lions have been found to exhibit different personality traits in captivity [21][22][23]. In this study, we found that the lions differed in their response to construction work, with the male lion increasing time spent pacing during the construction period, whilst the females exhibited no change in pacing.…”
Section: Discussionmentioning
confidence: 99%
“…Dominance loaded positively and strongly for behavioural traits -bold, bullying, dominant, aggressive to people, inventive, jealous and tense, while the behavioural traits affectionate, gentle, stable, submissive and trusting loaded negatively. Previous studies rated reintroduced African lions for their boldness [18] and Asiatic lions on a bold-shy axis between individuals raised in captivity and others that were wildrescued [15]. Personality traits in African lions that correlate with subjective wellbeing indicate that their social structure is important for wellbeing, especially in terms of the Dominance structure found in this species.…”
Section: Personality Of Lions At Zambi Wildlife Retreat and Sydney Zoomentioning
confidence: 90%
“…In captivity, the welfare of these lions is a considerable concern, as it is difficult to mimic their wide-ranging natural habitat [13]. A variety of behavioural tests and checklists have been developed in the past decade to help identify traits of wellbeing and the personalities among big cats (Vaz et al, in press); these tests and checklists have been used for lions [14][15][16][17][18], tigers [19][20][21], jaguars [22], cheetahs [23][24][25][26], snow leopards [27,28], and in particular the Asiatic lion personality [15,17] and African lion personality [14,16,18]. Similarly, studies have tried to understand the stress physiology and variation in GCs for lions [29][30][31].…”
Section: Introductionmentioning
confidence: 99%